Mineral transformation, ash formation and characterisation during pulverised fuel combustion - Silvester, Laurence Paul Joseph (2020)
Due to the growing concerns about climate change, the power generation sector is increasingly facing pressure to reduce greenhouse gas emissions whilst maintaining energy security and supply. Co-firing biomass with coal is considered an intermediate term solution that can reduce CO2 emissions from fossil fuel utilisation and maintain use of existing power plant infrastructure. For power generators, ash deposition is still a major cause of reduced boiler efficiency and unscheduled shutdowns on heat transfer surfaces, and historically, less attention has focused on deposition due to biomass co-firing.